THE DISCLOSURE OF DARK HUMOR AND COMEDIC SOCIOPATHY THROUGH INCONGRUITIES MADE BY THE VILLAIN THE JOKER IN THE DARK KNIGHT MOVIE - Max Nicholai Tesla; Indah Wahyuningsih; Sabta Diana (Haluan Sastra Budaya, 2020)
This study examines dark jokes and how they are delivered through implications made by a character named The Joker under the scope of Pragmatics in Incongruity Theory by Morreall (1987), and Attardo (1994). This study is also supported by some other theories such as Gricean Maxim by Grice (1989) and Conversational Implicature by Levinson (1983). The study is a descriptive-qualitative research with case study as the strategy. The data are obtained using documentary method by watching the movie The Dark Knight and selecting utterances made by The Joker that contain dark jokes. The findings of the study show that The Joker has many ways of delivering his dark joke as a display of his sociopathic character. The incongruities and the maxims he flouts vary, although there is dominance in ignorance type of incongruity and the flouting of maxim of quality. The reasons why The Joker makes dark jokes are because he enjoys the misfortunes of others and he sees them as entertainment as a sociopath that he is; he wants to shift the threats pointed to him and uses the jokes as the way for him to threaten his enemies back; and because he want to maintain unpredictability of his evil deeds by telling jokes with a dark twist at the end, just before he commits acts of crime. He uses a lot of implicatures to confuse his opponents and to keep them from understanding the way The Joker thinks and acts.